2018
DOI: 10.1101/285205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin features constrain structural variation across evolutionary timescales

Abstract: Abstract:The potential impact of structural variants includes not only the duplication or deletion of coding sequences, but also the perturbation of non-coding DNA regulatory elements and structural chromatin features, including topological domains (TADs). Structural variants disrupting TAD boundaries have been implicated both in cancer and developmental disease; this likely occurs via 'enhancer hijacking', whereby removal of the TAD boundary exposes enhancers to new target transcription start sites (TSSs). Wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 54 publications
3
30
0
Order By: Relevance
“…We also revealed that highly conserved boundaries are located near important developmental genes, suggesting that rearrangements that cause misregulation of these genes were likely negatively selected. Consistent with this observation, a recent study showed that both evolutionary fixed deletions in the great apes and deletions segregating in the human population are depleted at TAD boundaries, whereas deletions implicated in disease, such as neurodevelopmental disorders, do not show this constraint (Fudenberg and Pollard 2018). Overall, our findings suggest that both models may have been at play during the evolution of the gibbon genome, but further studies are required to test these paradigms, for example, by directly examining TAD boundary fragility in vitro (Canela et al 2017) and testing selection models across different species with rearranged genomes.…”
Section: Gibbon Breakpoints Overlap Boundaries Of Tadsmentioning
confidence: 58%
“…We also revealed that highly conserved boundaries are located near important developmental genes, suggesting that rearrangements that cause misregulation of these genes were likely negatively selected. Consistent with this observation, a recent study showed that both evolutionary fixed deletions in the great apes and deletions segregating in the human population are depleted at TAD boundaries, whereas deletions implicated in disease, such as neurodevelopmental disorders, do not show this constraint (Fudenberg and Pollard 2018). Overall, our findings suggest that both models may have been at play during the evolution of the gibbon genome, but further studies are required to test these paradigms, for example, by directly examining TAD boundary fragility in vitro (Canela et al 2017) and testing selection models across different species with rearranged genomes.…”
Section: Gibbon Breakpoints Overlap Boundaries Of Tadsmentioning
confidence: 58%
“…Previous studies [ 23 26 ] have shown that the distribution of somatic and germline SVs depends on a complex interplay among different mechanistic biases, originating from underlying chromosome conformations [ 25 ], DNA accessibility [ 24 , 27 ], functional embedding [ 5 ], methylation profiles [ 26 ], and cross-species conservation. For instance, disease SVs disrupt topologically associated domains (TADs) that influence the gene-enhancer interaction, leading to various diseases [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, disease SVs disrupt topologically associated domains (TADs) that influence the gene-enhancer interaction, leading to various diseases [ 25 ]. Similarly, the methylation status [ 26 ] and DNA accessibility [ 27 ] of genomic regions have been previously associated with the emergence of somatic and germline SVs. Furthermore, the disruption of coding and noncoding genomic elements—including promoters, untranslated regions (UTRs), and enhancers—along with the disruption of highly conserved genomic regions is likely to play a critical role in disease progression [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some kind of weighting scale would also help—it may be obvious to a physician that a particular HPO is not central to a patient's phenotype, but at present, that information is often not available in the record. The role of variants affecting so far poorly understood the function, particularly those that may affect chromatin structure. Examples of these have already been found in cancer (Fudenberg & Pollard, ; Makova & Hardison, ). It is not clear how well general noncoding impact methods will work on such variants, and they may be very far from genes, requiring a much larger total number of variants to be considered, with an accompanying rise in false positives.…”
Section: Discussionmentioning
confidence: 84%